Healthy ageing and spermatogenesis. Issue 4 (April 2021) - Pohl, Eva; Gromoll, Jörg; Wistuba, Joachim; Laurentino, Sandra
Abstract : Delayed family planning and increased parental age increase the risk for infertility and impaired offspring health. While the impact of ageing on oogenesis is well studied, this is less understood on spermatogenesis. Assessing ageing effects on the male germline presents a challenge in differentiating between the effects of ageing-associated morbidities, infertility and 'pure' ageing. However, understanding the impact of ageing on male germ cells requires the separation of age from other factors. In this review, we therefore discuss the current knowledge on healthy ageing and spermatogenesis. Male ageing has been previously associated with declining sperm parameters, disrupted hormone secretion and increased time-to-pregnancy, among others. However, recent data show that healthy ageing does not deteriorate testicular function in terms of hormone production and spermatogenic output. In addition, intrinsic, age-dependent, highly specific processes occur in ageing germ cells that are clearly distinct from somatic ageing. Changes in spermatogonial stem cell populations indicate compensation for stem cell exhaustion. Alterations in the stem cell niche and molecular ageing signatures in sperm can be observed in ageing fertile men. DNA fragmentation rates as well as changes in DNA methylation patterns and increased telomere length are hallmarks of ageing sperm. Taken together, we propose a putative link between the re-activation of quiescent Adark spermatogonia and molecular changes in aged sperm descending from these activated spermatogonia. We suggest a baseline of 'pure' age effects in male germ cells which can be used for subsequent studies in which the impact of infertility or co-morbidities will be studied.